Citrus tristeza virus Promotes the Acquisition and Transmission of ‘Candidatus Liberibacter Asiaticus’ by Diaphorina citri - Longtong Chen; Yangyang Liu; Fengnian Wu; Jingtian Zhang; Xiaoqing Cui; Shitong Wu; Xiaoling Deng; Meirong Xu (Viruses, 2023)
Diaphorina citri Kuwayama (D. citri) is an insect vector of phloem-limited ‘Candidatus Liberibacter asiatus’ (CLas), the presumed pathogen of citrus Huanglongbing (HLB). Recently, our lab has preliminarily found it acquired and transmitted Citrus tristeza virus (CTV), which was previously suggested to be vectored by species of aphids. However, the influences of one of the pathogens on the acquisition and transmission efficiency of the other pathogen remain unknown. In this study, CLas and CTV acquisition and transmission by D. citri at different development stages under field and laboratory conditions were determined. CTV could be detected from the nymphs, adults, and honeydew of D. citri but not from the eggs and exuviates of them. CLas in plants might inhibit CTV acquisition by D. citri as lower CTV–positive rates and CTV titers were detected in D. citri collected from HLB-affected trees compared to those from CLas–free trees. D. citri were more likely to obtain CTV than CLas from host plants co-infected with the two pathogens. Intriguingly, CTV in D. citri facilitated the acquisition and transmission of CLas, but CLas carried by D. citri had no significant effect on the transmission of CTV by the same vector. Molecular detection and microscopy methods confirmed the enrichment of CTV in the midgut after a 72-h acquisition access period. Collectively, these results raise essential scientific questions for further research on the molecular mechanism of pathogen transmission by D. citri and provide new ideas for the comprehensive prevention and control of HLB and CTV.